Nurturing Young Minds: Raising Environmental Awareness Through Digital Media and Education - Ari Widhiatama, Daniel; Brameswari, Catharina (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This research aims to empower young people by enhancing their awareness of environmental issues. Employing a learning ecology framework and a narrative inquiry approach, the researchers collaborated with lecturers from a private university in Yogyakarta, asking them to engage students in environmental learning and classroom activities that promote ecological awareness. This includes integrating ecological literacy into environmental education and incorporating the role of digital media and technology to enhance learning outcomes, especially in Content and Language Integrated Learning (CLIL) classes. The present study also examines the use of digital media as a medium to recognize and challenge environment issues around them. Adopting a descriptive qualitative approach, the researchers explored the students’ experiences regarding the use of digital media in speaking classes. Furthermore, data sources were primarily collected from students’ assignments, projects, reflection notes, questionnaire, and interview transcripts. The findings revealed three key aspects. Firstly, this research uncovers how students perceive the use of technology in addressing waste management issues in their surroundings. Secondly, it explores the classroom activities and reflections that emerge when students engage with environmental-themed digital media. Thirdly, the study highlights that these classroom activities, assignments, and projects increase their environmental values and awareness.